Molecular Mechanisms of Epileptic Encephalopathy Caused by KCNMA1 Loss-of-Function Mutations - Yao, Yu; Qu, Dongxiao; Jing, Xiaoping; Jia, Yuxiang; Zhong, Qi; Zhuo, Limin; Chen, Xingxing; Li, Guoyi; Tang, Lele; Zhu, Yudan; Zhang, Xuemei; Ji, Yonghua; et al. (Frontiers in Pharmacology, 2022)
The gene kcnma1 encodes the α-subunit of high-conductance calcium- and voltage-dependent K+ (BK) potassium channel. With the development of generation gene sequencing technology, many KCNMA1 mutants have been identified and are more closely related to generalized epilepsy and paroxysmal dyskinesia. Here, we performed a genetic screen of 26 patients with febrile seizures and identified a novel mutation of KCNMA1 (E155Q). Electrophysiological characterization of different KCNMA1 mutants in HEK 293T cells, the previously-reported R458T and E884K variants (not yet determined), as well as the newly-found E155Q variant, revealed that the current density amplitude of all the above variants was significantly smaller than that of the wild-type (WT) channel. All the above variants caused a positive shift of the I-V curve and played a role through the loss-of-function (LOF) mechanism. Moreover, the β4 subunit slowed down the activation of the E155Q mutant. Then, we used kcnma1 knockout (BK KO) mice as the overall animal model of LOF mutants. It was found that BK KO mice had spontaneous epilepsy, motor impairment, autophagic dysfunction, abnormal electroencephalogram (EEG) signals, as well as possible anxiety and cognitive impairment. In addition, we performed transcriptomic analysis on the hippocampus and cortex of BK KO and WT mice. We identified many differentially expressed genes (DEGs). Eight dysregulated genes [i.e., (Gfap and Grm3 associated with astrocyte activation) (Alpl and Nlrp10 associated with neuroinflammation) (Efna5 and Reln associated with epilepsy) (Cdkn1a and Nr4a1 associated with autophagy)] were validated by RT-PCR, which showed a high concordance with transcriptomic analysis. Calcium imaging results suggested that BK might regulate the autophagy pathway from TRPML1. In conclusion, our study indicated that newly-found point E155Q resulted in a novel loss-of-function variant and the dysregulation of gene expression, especially astrocyte activation, neuroinflammation and autophagy, might be the molecular mechanism of BK-LOF meditated epilepsy.